458 Pulsed Electromagnetic Fields (PEMF) Used in Cervical Spine Fusion for Patients with Risk Factors for Non-Union. (1st April 2022) - Wind, Joshua J.; Weinstein, Marc; Radcliff, Kris; Lansford, Todd; Aleem, Ilyas; Patel, Vikas V.; Vokshoor, Amir A.
Abstract : INTRODUCTION: A post market prospective study was conducted to examine the effect of the adjunctive use of a pulsed electromagnetic field (PEMF) device on cervical fusion rate in subjects with risk factors for non-union. PEMF has been shown to stimulate bone healing and can be a valuable tool to help overcome biological deficiencies in patients at risk for non-union. METHODS: Patients undergoing cervical fusion surgery were identified for enrollment from 11 investigator sites based on being classified as having one or more risk factors for non-union. Subjects were those having a multi-level (2 or more) fusion, prior cervical spine fusion, diabetes, osteoporosis, or smokers. Subjects were required to wear the PEMF device for 4 hours/day for 6 months. Compliance was measured based on usage data downloaded from the device. The primary outcome measure was fusion status at 12 month follow-up period as indicated by x-ray and CT. Fusion status was determined by the site investigator using A/P, lateral, and flexion/extension radiographs in addition to CT (without contrast). RESULTS: Out of 152 subjects, 138 (90.8%) were graded as fused (all levels) at the 12 month visit About half of the subjects (49.3%) had 3 or more levels fused. Fusion success for subjects with 2 or more risk factors was 88.5%, and was 94.4% for subjects with a single risk factor. On average, compliance rates (minutes using device/minutes prescribed) were 83.8% and 74.9% for the 3 and 6 month visit, respectively. The followup rate at the 12 month visit was 97%. CONCLUSION: The results of our study suggest that adjunctive use of PEMF is effective in cervical spine fusion patients with factors associated with non-union. Favorable fusion rates were obtained with patients having elevated comorbidity and/or complex surgeries. Further research is planned to include a control group in a real world setting to better assess the impact of the PEMF device in this population.